2019
DOI: 10.1111/apa.15053
|View full text |Cite
|
Sign up to set email alerts
|

Later puberty onset among chronically undernourished adolescents living in a Karachi slum, Pakistan

Abstract: The timing of puberty onset, an important pubertal milestone, is frequently used to evaluate the general health of a population with an important impact on future health. Despite increased global attention to adolescent research, there is currently little interest in scientific research dedicated to puberty. Most recently, Deardorff et al 1 stress the importance of puberty research in understudied populations including diverse ethnic groups, boys and sexual minority youth. Research on puberty among children wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…However, we could not provide evidence for the causality between puberty development and anemia due to the cross-sectional design. Based on a cohort study in Pakistan, Campisi and colleagues reported that anemia and stunting in childhood can delay the adolescent puberty onset [41]. We hypothesized that among female adolescents, those who had puberty onset may have better nutrition status and lower risk of anemia, on the other hand the onset of puberty among those with better nutritional status was associated with regular blood loss and higher risk of anemia, which potentially resulted in the null associations between puberty development and anemia among females.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not provide evidence for the causality between puberty development and anemia due to the cross-sectional design. Based on a cohort study in Pakistan, Campisi and colleagues reported that anemia and stunting in childhood can delay the adolescent puberty onset [41]. We hypothesized that among female adolescents, those who had puberty onset may have better nutrition status and lower risk of anemia, on the other hand the onset of puberty among those with better nutritional status was associated with regular blood loss and higher risk of anemia, which potentially resulted in the null associations between puberty development and anemia among females.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not provide evidence for the causality between puberty development and anemia due to the cross-sectional design. Based on a cohort study in Pakistan, Campisi and colleagues reported that anemia and stunting in childhood can delay the adolescent puberty onset [37]. We hypothesized that among female adolescents, those who had puberty onset may have better nutrition status and lower risk of anemia, on the other hand the onset of puberty among those with better nutritional status was associated with regular blood loss and risk of anemia, which potentially resulted in the null associations between puberty development and anemia among females.…”
Section: Discussionmentioning
confidence: 96%
“…However, we could not provide evidence for the causality between puberty development and anemia due to the cross-sectional design. Based on a cohort study in Pakistan, Campisi and colleagues reported that anemia and stunting in childhood could delay the adolescent puberty onset [34]. We hypothesized that among female adolescents, those who had puberty onset would have better nutrition status and lower risk of anemia, but the onset of puberty was associated with regular blood loss and higher risk of anemia, consequently resulting in the null associations between puberty development and anemia.…”
Section: Discussionmentioning
confidence: 97%